The S2 stream: the shreds of a primitive dwarf galaxy. Issue 1 (20th October 2020) - Aguado, David S; Myeong, G C; Belokurov, Vasily; Evans, N Wyn; Koposov, Sergey E; Allende Prieto, Carlos; Lanfranchi, Gustavo A; Matteucci, Francesca; Shetrone, Matthew; Sbordone, Luca; Navarrete, Camila; González Hernández, Jonay I; et al.
ABSTRACT: The S2 stream is a kinematically cold stream that is plunging downwards through the Galactic disc. It may be part of a hotter and more diffuse structure called the Helmi stream. We present a multi-instrument chemical analysis of the stars in the metal-poor S2 stream using both high- and low-resolution spectroscopy, complemented with a re-analysis of the archival data to give a total sample of 62 S2 members. Our high-resolution program provides α-elements (C, Mg, Si, Ca, and Ti), iron-peak elements (V, Cr, Mn, Fe, Ni), n-capture process elements (Sr, Ba), and other elements such as Li, Na, Al, and Sc for a subsample of S2 objects. We report coherent abundance patterns over a large metallicity spread (∼1 dex) confirming that the S2 stream was produced by a disrupted dwarf galaxy. The combination of S2's α-elements displays a mildly decreasing trend with increasing metallicity, which can be tentatively interpreted as a 'knee' at [Fe/H] < −2. At the low-metallicity end, the n-capture elements in S2 may be dominated by r-process production; however, several stars are Ba-enhanced but unusually poor in Sr. Moreover, some of the low-[Fe/H] stars appear to be carbon-enhanced. We interpret the observed abundance patterns with the help of chemical evolution models that demonstrate the need for modest star formation efficiency and low wind efficiency confirming that the progenitor of S2 was a primitive dwarf galaxy.